1990
DOI: 10.1530/acta.0.1230643
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor in mice: changes during circadian and female reproductive cycles

Abstract: To clarify the variation of mouse epidermal growth factor production during the 24-h and female reproductive cycles, we measured its concentrations in the plasma, submandibular salivary gland, urine, kidneys and liver of adult male and female mice during consecutive 12-h dark and 12-h light periods, different stages of pregnancy, and lactation. The concentration of epidermal growth factor in the submandibular gland showed no circadian changes. In plasma and in the liver it increased during the dark period, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…EGF is also present in maternal mouse blood throughout pregnancy, but its concentration appears to be very low. In most cases, plasma EGF concentration was <150 pg/ml (29)(30)(31), although values as high as about 5 ng/ml have been reported for some individuals (30). Since the lowest concentration of EGF that affected mPL-I and mPL-II secretion was 1 ng/ml, it is not clear whether circulating EGF plays a significant role in regulating mPL-I and mPL-II secretion in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…EGF is also present in maternal mouse blood throughout pregnancy, but its concentration appears to be very low. In most cases, plasma EGF concentration was <150 pg/ml (29)(30)(31), although values as high as about 5 ng/ml have been reported for some individuals (30). Since the lowest concentration of EGF that affected mPL-I and mPL-II secretion was 1 ng/ml, it is not clear whether circulating EGF plays a significant role in regulating mPL-I and mPL-II secretion in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Early reports in mice have demonstrated lower plasma EGF levels in females compared to males [42]. Further, plasma EGF levels in female mice are altered by the circadian rhythm, pregnancy, [53] and are increased with testosterone treatment [52]. Although 17-β estradiol is protective against brain endothelial damage in vitro [38], perhaps the male sex hormones exert a greater protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ErbB1 receptors are abundant in liver [41, 42] and that EGF has multiple effects on cultured hepatocytes including stimulation of glycolysis [43], suppression of PEPCK gene expression [9] and complex, substrate-dependent effects on gluconeogenesis [44]. Under certain conditions the concentrations of plasma EGF would be high enough to manifest such effects [45, 46]. But there is also experimental support for a role of hepatic ErbB receptors in liver regeneration and ligand clearance [41, 42].…”
Section: Discussionmentioning
confidence: 99%